Christologie in der Spannung zwischen biblischem Kerygma und konziliarer Lehre: Bemerkungen zu einem wichtigen Buch - Weß, Paul (Zeitschrift für katholische Theologie, 1998)
The article offers a critical evaluation of the book by H.-J. Schulz, Bekenntnis statt Dogma. Kriterien der Verbindlichkeit kirchlicher Lehre (QD 163). Freiburg i. Br. 1996. The author participates in the concern of Schulz, who tries to establish criteria, by which pronuntiations of the ecclesiastical authorities can be analised according to their obligatory character. However, he tries, starting from the new hermeneutical principles for our understandig of Scripture and Tradition, as established by the Second Vatican Council, to draw conclusions, which go further than the ones reached in the book by Schulz. This is shown above all with the example of the christological and trinitarian doctrines pronounced by the first ecumenical councils.